Influence of depression symptoms on serum tumor necrosis factor-α of patients with chronic low back pain - Wang, Haili; Ahrens, Carsten; Rief, Winfried; Gantz, Simone; Schiltenwolf, Marcus; Richter, Wiltrud (Arthritis Research & Therapy, 2010)
Patients with chronic low back pain (cLBP) have high rates of comorbid psychiatric disorders, mainly depression. Recent evidence suggests that depressive symptoms and pain, as interacting factors, have an effect on the circulating levels of inflammatory markers relevant to coronary artery disease. Our previous work showed a higher serum level of an inflammatory marker tumour necrosis factor-alpha (TNFα) in patients with cLBP, which did not correlate with intensity of low back pain alone. In the present study we investigated the cross-sectional associations of depressive symptoms, low back pain and their interaction with circulating levels of TNFα.
Gesehen am 10.10.2023